Targeting social learning and engagement: What serious games and gamification can offer to participatory modeling. (December 2020) - Bakhanova, Elena; Garcia, Jaime A.; Raffe, William L.; Voinov, Alexey
Abstract: Serious games and gamification are useful tools for learning and sustaining long-term engagement in the activities that are not meant to be entertaining. However, the application of game design in the participatory modeling context remains fragmented and mostly limited to user-friendly interfaces, storytelling, and visualization for better representation of the simulation models. This paper suggests possible extensions of game design use for each stage of the participatory modeling process, aiming at better learning, communication among stakeholders, and overall engagement. The proposed extensions are based on the effects that different types of game-like applications bring to the aspects of social learning and the contribution of gamification to engagement, motivation, and enjoyment of some activities. We conclude that serious games and gamification have a high potential for improving the quality of the participatory modeling process, while also highlighting additional research that is needed for designing particular practical gamified applications in this context. Highlights: Game-like applications contribute to different aspects of social learning. Gamification increases engagement, motivation, and enjoyment of an activity. Participatory modeling has been gamified mostly through interactive interfaces and role-play. There is no ready-to-go solution for gamification of participatory modeling. Gamified interventions should be customized to the context of participatory modeling stages.